PROGRAM PENGEMBANGAN KEPEMIMPINAN BAGI PEMIMPIN MUDA PADA LEMBAGA PENDIDIKAN NONFORMAL DI PAPUA - Lusiana Idawati (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
BEC is a nonformal education institution based in Jayapura and has several branches in Papua. It provides quality education for the local communities through a variety of courses, including English language, basic education, sempoa, and Montessori. Despite the Covid-19 pandemic, BEC has been growing fast in the last two years, which required organization structure’s adjustment and appointment of new leaders at the middle and entry-level management. The new leaders were young and most of them had little or no experience in leadership. To help equip them in their roles and responsibilities as leaders, a leadership development program was developed. The program was based on the Situational Leadership® II theory from Blanchard et al. and delivered through a six-week training and coaching method that took place from March to April 2023. The results of the program were the organization’s situational mapping based on commitment and competencies of its talents, and the implementation of SL II-based leadership behaviors in the organization. Participants of the program became more intentional and committed in developing their teams and achieving common goals, and more confident to further develop BEC and contribute to the development of the communities in Papua through education.Keywords: Leadership Development Program, Nonformal Education Center, Situational Leadership, Young Leaders